Susceptibility to Stress Corrosion of Laser-Welded Composite Arch Wire in Acid Artificial Saliva - Chao Zhang; Xinhua Sun (Advances in Materials Science and Engineering)
The corrosion resistance of laser-welded composite arch wire (CoAW) with Cu interlayer between NiTi shape memory alloy and stainless steel wire in artificial saliva with different acidities and loads was studied. It was found that both the solution pH and the stress had a significant influence on the corrosion behaviors of the CoAW samples. Decreasing the solution pH or increasing the loading stress caused the increase of Cu release and weight loss. The corroded morphology formed on the surfaces of the CoAW was the consequence under the combined effect of corrosion and stress.